Fluid-dynamic concept of oil and gas generation. Principles (discussion) - E. A. Ablya (Georesursy, 2024)
The Principles of the fluid-dynamic concept of oil and gas formation, which expands the ideas of the previously proposed of the same name model in co-authorship, are presented. The base of the concept – simultaneity of processes, which, in the presence of a significant vertical flow of fluids and heat, cause the emergence of structures, a new reservoirs and new dynamic barriers, oil and gas formation and the formation of deposits. The formation of certain types of sedimentary basins and then the selective formation of their “traditional industrial” oil and gas content from predominantly fossilized living matter are predetermined by the development of deep, not only specific crustal, but also mantle processes. Based on the theory of open non-equilibrium systems, the concept assumes vertical tectonopetrological stratification and alternation of de-compaction and compaction zones in the lithosphere and upper mantle, when disclosed, “catastrophic” heat-mass transfer of fluids from decompacted zones and pulsation oil formation are carried out not from the entire source organic matter, but only from the oil “semi-finished product”, and not from the basin as a whole, but in its individual parts.